TINJAUAN YURIDIS PENYEWAAN PULAU DI WILAYAH KEDAULATAN REPUBLIK INDONESIA TERHADAP PIHAK ASING BERDASARKAN UNITED NATIONS CONVENTION ON THE LAW OF THE SEA (UNCLOS) 1982 - Prima Agung Hermanda; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Island rentals in Indonesia to foreign parties violate the principles of an island nation that emphasizes the integration between land, sea and air dimensions in carrying out national development. It can also eliminate the integration of the sea dimension or waters in national development. in the National Long-Term Development Plan (RPJPN), one of the points of the long-term development mission is to realize Indonesia as an archipelago / maritime country, while the nation's predecessors have fought steadily so that the principles of the island nation are recognized byinternational world as stated in UNCLOS 1982.This type of research used in writing this law is normative legal research that focuses on principles by formulating legal principles, both from social data and from positive written legal data. Whereas when viewed from the nature of this research is descriptive. this study uses secondary data, namely data that has been prepared.The results of this study are island leasing in the territory of the Republic of Indonesia sovereignty against foreign parties based on the 1982 United Nations Convention on Law of the Sea (UNCLOS) in the form of usufructuary rights and leases based on legislation that applies in the Republican sovereignty Indonesia. Indonesian foreign parties are given authority over island rentals as limited as managers. However, some foreign parties have exceeded the authority given to the detriment of the local people who are the people of Indonesia. Island leasing in the territory of the Republic of Indonesia sovereignty against foreign parties based on positive law in Indonesia has not been able to accommodate the interests of the Indonesian people in accordance with the 1945 ConstitutionIsland leasing to foreign parties is more oriented towards seeking profits to increase state income and naturally eliminate the rights of local communities over natural resources of Indonesian waters.Keywords: Island Rental, Foreign Parties, UNCLOS 1982